Development Accounting: Conceptually Flawed and Inconsistent with Empirical Evidence (2014)
Development accounting depends on two simplifying assumptions, that economies can be represented by a common aggregate production function and that aggregate factors of production are paid their social marginal products. An aggregate production function can explain income across countries, but the mathematics of the aggregate production function and the empirical evidence both indicate that aggregate factors are paid a small fraction of their social marginal products. As a consequence, development accounting underestimates the income differences due to human capital and overestimates the differences due to TFP. This error cannot be corrected because human capital’s social marginal product is not observable.